Peran Yatim Mandiri Kudus Dalam Meningkatkan Kesejahteraan Janda Miskin Melalui Program Kampung Mandiri Di Desa Cangkring Karanganyar Demak - Riyadi, Fuad; Ramadhanti, Firda (ZISWAF, 2020)
The purpose of this research is to analyze the role of the Amil Zakat Institution (LAZ) in the economic sector to improve the welfare of poor widowed families, namely through the economic empowerment program of the Kampung Mandiri National Amil Zakat Institute (LAZNAS) Yatim Mandiri, Kudus Branch located in Cangkring B Village, Karanganyar District, Regency. Demak. The results showed that the LAZNAS Yatim Mandiri Kudus Branch program in the formation of the Kampung Mandiri program, namely first, planning the formation of the Kampung Mandiri program in Cangkring B Village Karanganyar Demak to the implementation of the program, with the business being managed is fried onions with the branding "Guemez Onions". Second, the distribution of funds for the Kampung Mandiri program is budgeted at Rp. 128,590,000 for capital and program facilities and infrastructure. Third, monitoring the Kampung Mandiri program. The role of the Kampung Mandiri program for poor widows is first, to provide knowledge of entrepreneurship and Islam. Second, increase entrepreneurial skills. Third, increase income. The role of LAZNAS Yatim Mandiri, Kudus Branch is still not optimal in improving the welfare of poor widow families because the income earned from working wages when the production of fried onions is of little value, and the profits from sales cannot be used directly by widows because they are still collected and stored first. The Kampung Mandiri program has been supported by the existence of village approval, grants for program activities, and business capital from LAZNAS Yatim Mandiri Kudus Branch. Meanwhile, the obstacles experienced are the slow rate of development, the production process is not yet optimal, the lack of cohesiveness of the members of Kampung Mandiri, and the marketing of products that are not optimal.